Alonzo's war : letters from a young Civil War soldier - Searing, Alonzo Bryant, 1844-1932 (Fairleigh Dickinson University Press ; Rowman & Littlefield Pub. Group, 2012)
"Alonzo Bryant Searing, a high school graduate aged 18, enlisted in the 11th New Jersey Volunteer Regiment in Dover, New Jersey in 1862 and served two years and ten months as a Private in the Union Army. His unit served in 27 engagements and he was slightly wounded twice. During that time he wrote 110 letters home to his sister. Twenty-five years later he edited these letters, adding information from his well-kept journals and his memory and had them published in The Morris County Journal newspaper from 1890-1893. The book is this collection of letters, written with a dry humor, which includes graphic descriptions of engagements, including some listings of death, wounding and sickness, opinions of the war, politics, religion, race, alcohol, deserters, camp conditions, hospital life, his own poetry and accounts of meetings with friends and relatives in nearby Army units."--Provided by publisher.